2007
DOI: 10.1099/ijs.0.64801-0
|View full text |Cite
|
Sign up to set email alerts
|

Thalassococcus halodurans gen. nov., sp. nov., a novel halotolerant member of the Roseobacter clade isolated from the marine sponge Halichondria panicea at Friday Harbor, USA

Abstract: A Gram-negative, non-pigmented, ovoid-shaped, strictly aerobic, catalase- and oxidase-positive and highly halotolerant bacterial strain that was devoid of swimming and gliding motility, designated UST050418-052T, was isolated from the surface of the marine sponge Halichondria panicea at Friday Harbor, WA, USA. Strain UST050418-052T required NaCl for growth and could tolerate salt concentrations of up to 18 %. The primary respiratory quinone was ubiquinone-10 and the DNA G+C content was 57.8 mol%. The predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…In addition, the low level of similarity of some of our sequences with sequences in the GenBank database indicated that there is an unexplored bacterial group in sponges and the potential of identifying novel bacteria. In fact, we have already identified two novel bacteria isolated from M. incrustans (23) and H. panicea (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the low level of similarity of some of our sequences with sequences in the GenBank database indicated that there is an unexplored bacterial group in sponges and the potential of identifying novel bacteria. In fact, we have already identified two novel bacteria isolated from M. incrustans (23) and H. panicea (24).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, fluorescence in situ hybridisation studies have been used to identify numerous bacterial phyla closely associated with sponges [40]. Other culture-independent studies employed PCR amplification of bacterial 16S rRNA genes directly from sponge metagenomic DNA followed by denaturing gradient gel electrophoresis [22,48] or restriction fragment length polymorphism analyses [23,61]. Cloning and sequencing of 16S rRNA genes has also been used in many microbial diversity investigations from a wide range of sponge species [5,11,15,27,35,42,[51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have led to the isolation of novel bacterial genera and species from other phyla also. Novel α-Proteobacteria [22], γ-Proteobacteria [8,21,36,37], Bacteroidetes [17][18][19][20] and Verrucomicrobia [39,59] have all been cultured from sponge tissues. There is growing evidence that monophyletic bacterial lineages have co-evolved with their sponge hosts to form sponge-specific clades which are more similar to each other than to similar taxa from non-sponge sources [24,47,54].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Primorskyibacter , which was proposed by Romanenko et al (2011), comprises a single recognized species, Primorskyibacter sedentarius . The genus Thalassococcus was proposed by Lee et al (2007) and comprises two species with validly published names, Thalassococcus halodurans (Lee et al , 2007) and Thalassococcus lentus (Park et al , 2013). The two genera have been isolated from marine environments (Lee et al , 2007; Romanenko et al , 2011; Park et al , 2013).…”
mentioning
confidence: 99%